Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1264/jsme2.22.232
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anammox Activity and Diversity of Anammox Bacteria-Related 16S rRNA Genes in Coastal Marine Sediment in Japan

Abstract: A first assessment of anammox activity, which is a unique N2 emission process, was conducted in samples of coastal marine sediment from Japan with a 15 N tracer. The occurrence and diversity of bacteria possibly responsible for the anammox process were also evaluated by selective PCR-amplification of the 16S rRNA gene for known anammox bacteria. Anammox activity, detected by measuring 14 N 15 N gas production, was only found in samples collected at the intertidal sand bank located at the Yodo River estuary. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
108
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 35 publications
4
108
3
Order By: Relevance
“…Although Amano et al recently reported that anammox activity and anammox-related bacteria were detected in coastal marine sediments in Japan, 12) the anammox-related bacterial clones detected in this study (Fig. 2) were different from those reported in their paper.…”
contrasting
confidence: 99%
“…Although Amano et al recently reported that anammox activity and anammox-related bacteria were detected in coastal marine sediments in Japan, 12) the anammox-related bacterial clones detected in this study (Fig. 2) were different from those reported in their paper.…”
contrasting
confidence: 99%
“…Since the discovery of anammox in the sea bed of a continental shelf slope (29), an increasing number of reports have demonstrated that the pathway is present in various marine ecosystems and may involve in the nitrogen cycle (7,24). A few studies reported anammox activity in freshwater and estuarine sediments (2,3,6,16,18,30) as well as in anoxic water columns of permanently stratified lakes in tropical (25) and temperate areas (9). However, the significance and diversity of anammox bacterial populations in freshwater ecosystems are not fully understood.…”
mentioning
confidence: 99%
“…Twelve primer combinations (Table 1; Inqaba Biotec, South Africa) obtained from literature were selected to test for the presence of different anammox species. The 50 μℓ PCR reaction contained 200 μM of each deoxynucleotide triphosphate, 0.25 μM of each primer, 2 mM MgCl 2 , 2.5 U Taq DNA polymerase (Fermentas Life Sciences, EU) and approximately 100 ng of template DNA (adapted from Amano et al, 2007). The PCR amplification was initiated with a 4 min denaturation step at 94°C and concluded with a final 7 min elongation at 72°C.…”
Section: Amplification Of Relevant Gene Sequencesmentioning
confidence: 99%